Experimental waviness evolution of interstitial free - IF steel sheet under biaxial stretching - Bressan J.D.* (2015)
© (2015) Trans Tech Publications, Switzerland.The purpose of present study is to present experimental results and a mathematical model for the evolution of surface waviness parameters with plastic strain of Interstitial Free - IF steel sheet under uniaxial and biaxial stretching tests. Roughness and waviness are very important quality parameters to be evaluated in sheet metal forming. Various waviness profile parameters such as the arithmetic average waviness Wa, the total height peak-valley waviness Wt, maximum peak height Pp and maximum valley depth Pv were measured during uniaxial and biaxial tests. Tensile test specimens at 0°, 45° and 90° to the direction of rolling and Nakazima type specimens of IF steel were fabricated. After preparing the test specimens, incremental simple tensile and Nakazima biaxial tests with flat punch were performed to characterize the negative and positive quadrant of the Map of Principal Surface Limit Strains, MPLS, of IF steel sheet. Measurements of waviness parameters of the specimen surface at incremental plastic strain stages were performed at the same surface site. Also, during the uniaxial and biaxial tests, the following plastic strains were calculated from printed circular mesh at each incremental step: ε1 longitudinal major strain and ε2 transverse minor strain. From these data, curves of waviness parameters versus equivalent strain ε¯ were plotted to obtain a phenomenological equation of 4th or 3rd degree polynomial type. Furthermore, the growth rates of Wa and Wt parameters with the equivalent plastic strain were assessed. From the growth rate curves, it was possible to verify how the sheet thickness imperfections evolves during straining, being possible to predict the influence of plastic strain on the waviness values of IF steel sheets. From the analysis of Wa and Wt growth rates during straining, it was possible to proposed a criteria for the onset of local necking or limit strains in the MPLS. The waviness parameters Wt is the best for characterizing the onset of local necking in sheet metal forming.